(untitled) (International Journal of Innovative Technologies in Economy, 2022)
The article analyzes the current trends in bank lending to small and medium-sized businesses in Ukraine and banking products and programs to help small and medium-sized businesses provided by individual state-owned banks. Conclusions on the current situation are substantiated and the directions of development of bank lending to small and medium business are determined.